Entrepreneurial Intention of a Senegalese Entrepreneur in a Brotherhood Context: Towards The Emergence of New "Atypical" Entrepreneurs - Hammouchi, Mohammed Said (European Scientific Journal, ESJ, 2018)
The purpose of this article is to understand the starting point of the intention of religious entrepreneurs, that we call "Atypical", for the simple reason that their entrepreneurial intentions include not only the economic aspect but there is also evidence of some foundation walls spiritual view of the context in which operate these entrepreneurs: the Tijanie brotherhood. These religious entrepreneurs create travel agencies specializing in the phenomenon of the "Zyaraâ€1. To do this, we will focus initially on generalities about highlighted Islam in Africa, and then we will introduce our paper on the emergence of the Tijaniyya brotherhood. In a second step, we will emphasize the economic dimension of the Tijaniyya, which includes both the phenomenon of the Â«ZyaraÂ», and trade which can arise; but also the emergence of atypical entrepreneurs in their entrepreneurial intentions through creative type travel "Zyaraâ€. Our epistemological positioning is interpretative; that is, we go from the field to interpret the intentions of these entrepreneurs, given the absence of literature dealing with entrepreneurship in a religious context. This means that our mode of reasoning is inductive; what brought us to do indepth interviews with this type of entrepreneurs in Senegal. This article presents concrete results concerning the entrepreneurial intentions of the religious entrepreneurs object of our present study. These intentions are religious orders, in the context of these entrepreneurs; on a categorized these intentions under five major axes; Â« Love and Propaganda of the Brotherhood ; Join the useful to the pleasant ; Respect and love of members of the brotherhood ; Self-achievement ; Tribal or family affiliation Â».